Unveiling Religious Moderation in Early Childhood Education in Indonesia: The Interplay of Agency and Hidden Curriculum in Kindergarten - Q. Abellana, El Chamberlain; Angga Pratama, Ryan; Zineb, El Atmani; Fitri Nugraheni, An Nisaa (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study investigates how religious moderation is cultivated in inclusive early childhood education through the interaction between agency and hidden curriculum, with particular attention to the roles of teachers, school leaders, parents, and children.Design/methods/approach – This study employed a qualitative case study design at TK Pedagogia Yogyakarta, an inclusive early childhood education institution in Yogyakarta, Indonesia, involving seven informants: one principal, four teachers, one parent, and one student. Data were collected through classroom and school observations, semi-structured interviews, and document analysis, and were analyzed using thematic analysis to examine how religious moderation was produced through everyday routines, interactions, and symbolic practices.Findings – The findings show that religious moderation was not formed primarily through formal instruction, but through the practical organization of school life. Teachers, school leaders, parents, and children collectively shaped inclusive dispositions through routines, relational practices, interfaith activities, and symbolic forms of participation embedded in the school culture. Values such as tolerance, balance, justice, cooperation, and respect for difference were internalized through repeated interaction, emotional safety, and dialogical learning. The hidden curriculum was central in mediating the institutional reproduction of moderation, enabling it to become socially embodied rather than merely declared as a normative ideal.Research implications/limitations – Based on a single inclusive institution under supportive conditions, the findings have limited transferability and do not fully capture power asymmetries, subtle exclusions, or children’s longer-term meaning-making. Future studies across diverse, culturally grounded contexts—particularly in Muslim societies—are needed to assess the stability, adaptability, and contestation of the identified mechanisms.Practical implications – Religious moderation in early childhood education cannot rely on curriculum alone; it depends on how pluralism is enacted through everyday pedagogy and institutional culture. Advancing this agenda requires integrated support in teacher preparation, relational climate, pedagogical resources, and family engagement to embed moderation as lived practice.Originality/value – This study shows that religious moderation is institutionally produced through the interaction of agency and the hidden curriculum, extending beyond formal curriculum discourse and foregrounding culturally grounded dynamics in Muslim and other underrepresented early childhood contexts.Paper type Research paper